พันธกรณีตามข้อบทเรื่องสิ่งแวดล้อมในความตกลงเขตการค้าเสรีทวิภาคี : ศึกษากรณีประเทศสหรัฐอเมริกาและประเทศชิลี - รุจิรา ญาณะเหล็ก (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The Environment Chapter in the US-Chile Free Trade Agreement has problems concerning clarifications of the regulations, as follow : there is no regulation to set a minimum standard in the environmental protection laws; there is no regulation to set the rules and details which are the guidance to effectively enforce environmental laws; there is only the regulation stating that it is inappropriate to encourage trade or investment by weakening or reducing the protections afforded in environmental laws but, on the other hand, whether or not the parties should encourage or increase the protections afforded in environmental laws by weakening trade or investment is not clear; there are no rules for that case; in the environment chapter, there is no enforcement hierarchy between the environment chapter and the others; in the recognition of paragraph 31 (i) of the Ministerial Declaration adopted on November 14, 2001 in Doha, WTO, which has the objective to negotiate the relationship between existing WTO rules and specific trade obligations set out in multilateral environmental agreements (MEAs), the Parties agree to take the result of such negotiation for adjustment to the Agreement. There is no clarified conclusion to the negotiation which means the environment chapter also has no clarification; and there is no rule in case of only one party being a party to MEAs which causes problems for that party fulfilling its obligations in the MEAs.The problem concerning clarification of the rules causes problems of interpretation when a dispute arises. The study of environmental disputes in North America Free Trade Agreement (NAFTA) found that interpretations tending to protect investment and trade were more likely than the protecting environment. The result of these interpretations has been that the environment chapter can not be put into practice, as well as causing problems for party to MEAs to conform to its MEAs obligations as well.